1326 Otorhinolaryngology Education and Training Innovation: A Literature Review of the Academic Year 2019-2020. (12th October 2021) - O'Hanlon, J; McKenna, J; Chan, J
Abstract: Aim: We aimed to summarise the literature on educational research and training in otorhinolaryngology during the academic year of 2019-2020. Method: A literature search was conducted on Medline, Embase and Cochrane in accordance with PRISMA guidelines for ""(ENT or otorhino* or otolaryngo* or (ear, nose, and throat)) and (educat* or train or training or teach*)"". The search was conducted independently on 13/09/20 by two authors (JOH, JM), any discrepancy was further reviewed by a third author (JC). All original research papers published between 2019-2020 were included. Results: 68 papers were included in our study. Educational research this year shifted focus on how to combat the negative impact of COVID-19 on otorhinolaryngology teaching. Although many of the interventions created for postgraduate and undergraduate education have not been formally assessed, virtual electives for medical students were found to increase interest and knowledge in the specialty. Surgical simulation represented the most common teaching method reported aside from COVID-19. 3D models were used for emergency training with an aim to increase trainee exposure to an anterior neck abscess, retrobulbar haematoma and paediatric tracheostomy. 3D models were positively rated for face and content validity and gave statistically significant improvements in confidence for trainees. Conclusions: The otorhinolaryngology training in 2019-2020 has changed massively due to the pandemic. Improving on virtual learning and adapting simulation training are the key to maintain a positive learning environment for medical students and doctors in the short term. Research on the effect of COVID-19 on otorhinolaryngology education and training will be the focus in 2021.